Multimodal imaging to aid in diagnosis of uveal effusion syndrome type 3. Issue 3 (2nd March 2021) - Markan, Ashish; Moharana, Bruttendu; Dogra, Mohit; Singh, Ramandeep
Abstract : A 47-year-old man presented to our retina clinic with gradual onset diminution of vision in his right eye for the last 3 months. Anterior segment evaluation was normal in both eyes. Fundus evaluation showed the presence of leopard spot appearance in the right eye with inferior exudative retinal detachment. Multimodal imaging was done to evaluate retinal pigment epithelium function, choroidal thickness, choroidal vascularity and scleral thickness. Multimodal imaging showed increased choroidal thickness, choroidal congestion on indocyanine green angiography and peripheral choroidal detachment with normal sclera thickness in our patient, thus pointing towards a diagnosis of uveal effusion syndrome type 3.